Malware detection framework based on graph variational autoencoder extracted embeddings from API-call graphs - Gunduz, Hakan (PeerJ. Computer science, 2022)
Malware harms the confidentiality and integrity of the information that causes material and moral damages to institutions or individuals. This study proposed a malware detection model based on API-call graphs and used Graph Variational Autoencoder (GVAE) to reduce the size of graph node features extracted from Android apk files. GVAE-reduced embeddings were fed to linear-based (SVM) and ensemble-based (LightGBM) models to finalize the malware detection process. To validate the effectiveness of the GVAE-reduced features, recursive feature elimination (RFE) and Fisher score (FS) were applied to select informative feature sets with the same sizes as GVAE-reduced embeddings. The results with RFE and FS selections revealed that LightGBM and RFE-selected 50 features achieved the highest accuracy (0.907) and F-measure (0.852) rates. When we used GVAE-reduced embeddings in the classification, there was an approximate increase of %4 in both models’ accuracy rates. The same performance increase occurred in F-measure rates which directly indicated the improvement in the discrimination powers of the models. The last conducted experiment that combined the strengths of RFE selection and GVAE led to a performance increase compared to only GVAE-reduced embeddings. RFE selection achieved an accuracy rate of 0.967 in LightGBM with the help of selected 30 relevant features from the combination of all GVAE-embeddings.